THE EFFECT OF DISCOUNT PRICES TOWARD IMPULSE BUYING HALAL FOOD ON GO FOOD CONSUMERS IN MEDAN - Dewi Andriany; Mutia Arda (Proceeding International Seminar of Islamic Studies, 2021)
During the Covid 19 pandemic it has caused changes in the lifestyle of consumers. The community is required to be able to carry out social distancing, which in turn demands that people do more activities from home. Due to limited space, many Muslim communities in Medan City use online applications such as Go Food to order halal food for their families. In general, they are more interested in ordering halal food because of the discount offered by Gojek. Of course this triggers high impulse buying for food product purchases during the Covid 19 period. Today's consumers are becoming more impulsive due to various factors. This study aims to prove the effect of discounts on impulsive purchases for consumers, especially on Go Food as one of the most visited applications. Primary data were collected through a questionnaire to 98 respondents. The analysis technique used is Simple Linear Regression. Based on the results of the analysis examining price discounts on impulsive purchases of Go Food consumers in Medan, it is concluded that price discounts significantly influence impulsive buying behavior among Go Food consumers in Medan.Keywords: Price Discounts, Impulsive Purchases, and Go Food.